(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In recent years, the widespread prevalence of rheumatoid arthritis among diseases of the connective tissue system and the development of disability in patients indicate the relevance of this disease. The development of disability in patients means that this disease is not only a medical, but also a social problem. In some cases, damage to internal organs may also occur, and many complications may develop. Approximately half of patients develop disability 3-5 years after the onset of the disease. Therefore, early diagnosis of this disease is very important. The article presents morphological changes in adrenal tissue during modeling of adjuvant arthritis in 30 white laboratory outbred rats. Under experimental conditions, dystrophic and destructive changes in the cellular elements of adrenal tissue were revealed.